The Use of Environmentally and Online-Based Media and Its Effect on PAI Learning Outcomes - Jasmawati Z (Program Pascasarjana UMSB, 2021)
Learning media has an important position for the achievement of learning outcomes, theoretically there are various types of media that are commonly used, therefore, researchers want to analyze the implementation of PAI learning using environmental-based and online-based learning media and their effect on PAI learning outcomes in state elementary schools. The collected data is analyzed using SPSS Version 20.0 through the Classical Assumption Test, Percentage Descriptive Analysis, T (partial) and F (simultaneous) Test. The results showed pai learning using Environmental-Based Media and Online supports the effective implementation of learning. This is evident from the percentage of respondents' answers of 90.83% for environmentally based media and 90.14% for online-based media. Based on the constant value of PAI Learning Media Based Environment and Online Based which amounted to 81,289. This constant value means, if there is no Environmentally Based and Online-Based PAI Learning Media, then a consistent value of Learners' Learning Outcomes of 81,289 will not appear.